127=27(r6)

Rewrite the equation as 27(r6)=127.

27(r6)=127

Divide each term in 27(r6)=127 by 27.

27(r6)27=127⋅127

Cancel the common factor of 27.

Cancel the common factor.

27r627=127⋅127

Divide r6 by 1.

r6=127⋅127

r6=127⋅127

Multiply 127⋅127.

Multiply 127 and 127.

r6=127⋅27

Multiply 27 by 27.

r6=1729

r6=1729

r6=1729

Take the 6th root of both sides of the equation to eliminate the exponent on the left side.

r=±17296

Simplify the right side of the equation.

Rewrite 17296 as 167296.

r=±167296

Any root of 1 is 1.

r=±17296

Simplify the denominator.

Rewrite 729 as 36.

r=±1366

Pull terms out from under the radical, assuming positive real numbers.

r=±13

r=±13

r=±13

The complete solution is the result of both the positive and negative portions of the solution.

First, use the positive value of the ± to find the first solution.

r=13

Next, use the negative value of the ± to find the second solution.

r=-13

The complete solution is the result of both the positive and negative portions of the solution.

r=13,-13

r=13,-13

r=13,-13

The result can be shown in multiple forms.

Exact Form:

r=13,-13

Decimal Form:

r=0.3‾,-0.3‾

Solve for r 1/27=27(r^6)